Effects of Lipid‐Lowering and Antihypertensive Treatments in Addition to Healthy Lifestyles in Primary Prevention: An Analysis of the HOPE‐3 Trial. Issue 15 (7th August 2018) - Dagenais, Gilles R.; Jung, Hyejung; Lonn, Eva; Bogaty, Peter M.; Dehghan, Mahshid; Held, Claes; Avezum, Alvaro; Jansky, Petr; Keltai, Matyàs; Leiter, Lawrence A.; Lopez‐Jaramillo, Patricio; Toff, William D.; et al.
Abstract : Background: It is not clear whether the effects of lipid‐lowering or antihypertensive medications are influenced by adherence to healthy lifestyle factors. We assessed the effects of both drug interventions in subgroups by the number of healthy lifestyle factors in participants in the HOPE‐3 (Heart Outcomes Prevention Evaluation) trial. Methods and Results: In this primary prevention trial, 4 healthy lifestyle factors (nonsmoking status, physical activity, optimal body weight, and healthy diet) were recorded in 12 521 participants who were at intermediate risk of cardiovascular disease (CVD) and were randomized to rosuvastatin, candesartan/hydrochlorothiazide, their combination, or matched placebos. Median follow‐up was 5.6 years. The outcome was a composite of CVD events. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression models. Participants with ≥2 healthy lifestyle factors had a lower rate of CVD compared with those with fewer factors (HR: 0.85; 95% CI, 0.73–1.00). Rosuvastatin reduced CVD events in participants with ≥2 healthy lifestyle factors (HR: 0.74; 95% CI, 0.62–0.90) and in participants with <2 factors (HR: 0.79; 95% CI, 0.61–1.01). Consistent results were observed with combination therapy (≥2 factors: HR: 0.74; 95% CI, 0.57–0.97; <2 factors: HR: 0.61; 95% CI, 0.43–0.88). Candesartan/hydrochlorothiazide tends to reduce CVD only in participants with <2 healthy lifestyle factors (HR: 0.78; 95% CI, 0.61–1.00). Conclusions: Healthy lifestyles are associated with lower CVD. Rosuvastatin alone and combined with candesartan/hydrochlorothiazide is beneficial regardless of healthy lifestyle status; however, the benefit of antihypertensive treatment appears to be limited to patients with less healthy lifestyles. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00239681.